The holy spirit and spirits in healing narratives of Zionist churches generating a grounded theory of mission praxis from a selection of case studies - Siwella, Edson Mbuzana (Stellenbosch : Stellenbosch University, 2015., 2015)
Thesis (PhD)--Stellenbosch University, 2015.